2021
DOI: 10.3390/ani11061842
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey on the Occurrence of Rickettsia spp., Neospora caninum, Bartonella henselae and Toxoplasma gondii in Cats from Tuscany (Central Italy)

Abstract: Asymptomatic cats often harbor pathogens, some of which have not been largely investigated in feline populations. The aim of this study was to evaluate the occurrence of antibodies against Rickettsia conorii, Rickettsia felis, Rickettsia typhi, Neospora caninum, Bartonella henselae and Toxoplasma gondii in cats from Tuscany. Ninety-five blood serum samples, previously collected, were analyzed by indirect immunofluorescence assay. Fifty-six (58.94%) cats had antibodies to at least one investigated pathogen: 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…According to the literature, positivity for N. caninum was observed from serological tests performed on captive and free-living felids (Ebani, Nardoni, Maestrini, Perrucci, & Mancianti, 2021). In the present study, we identified N. caninum in the brain of L. pardalis through molecular testing.…”
Section: Neosporasupporting
confidence: 50%
“…According to the literature, positivity for N. caninum was observed from serological tests performed on captive and free-living felids (Ebani, Nardoni, Maestrini, Perrucci, & Mancianti, 2021). In the present study, we identified N. caninum in the brain of L. pardalis through molecular testing.…”
Section: Neosporasupporting
confidence: 50%